The Influence of Emotional Intelligence and Career Development on Employee Performance - Shinta Oktafien; Bachtiar Usman; Sarfilianty Anggiani (CV. Syntax Corporation Indonesia, 2024)
This research is motivated by the low performance results shown by permanent lecturers at